Exploring the tertiary gene pool of bread wheat: sequence assembly and analysis of chromosome 5Mg of Aegilops geniculata. (November 2015) - Tiwari, Vijay K.; Wang, Shichen; Danilova, Tatiana; Koo, Dal Hoe; Vrána, Jan; Kubaláková, Marie; Hribova, Eva; Rawat, Nidhi; Kalia, Bhanu; Singh, Narinder; Friebe, Bernd; Doležel, Jaroslav; et al.
Summary: Next‐generation sequencing (NGS) provides a powerful tool for the discovery of important genes and alleles in crop plants and their wild relatives. Despite great advances in NGS technologies, whole‐genome shotgun sequencing is cost‐prohibitive for species with complex genomes. An attractive option is to reduce genome complexity to a single chromosome prior to sequencing. This work describes a strategy for studying the genomes of distant wild relatives of wheat by isolating single chromosomes from addition or substitution lines, followed by chromosome sorting using flow cytometry and sequencing of chromosomal DNA by NGS technology. We flow‐sorted chromosome 5M g from a wheat/ Aegilops geniculata disomic substitution line [DS5M g (5D)] and sequenced it using an Illumina HiSeq 2000 system at approximately 50 × coverage. Paired‐end sequences were assembled and used for structural and functional annotation. A total of 4236 genes were annotated on 5M g, in close agreement with the predicted number of genes on wheat chromosome 5D (4286). Single‐gene FISH indicated no major chromosomal rearrangements between chromosomes 5M g and 5D. Comparing chromosome 5M g with model grass genomes identified synteny blocks in Brachypodium distachyon, rice ( Oryza sativa ), sorghum ( Sorghum bicolor ) and barley ( Hordeum vulgare ). Chromosome 5M g ‐specific SNPs and cytogenetic probe‐based resources were developed and validated. Deletion bin‐mapped and ordered 5M g SNP markers will be useful to track 5M‐specific introgressions and translocations. This study provides a detailed sequence‐based analysis of the composition of a chromosome from a distant wild relative of bread wheat, and opens up opportunities to develop genomic resources for wild germplasm to facilitate crop improvement. Significance Statement: Wild relatives are rich sources of agronomically important genes and alleles, but hybridization barriers and poor genomic resources limit their use‐for crop improvement. Here we describe a strategy for studying the genome of a wild wheat relative by dissecting a single chromosome and sequencing it.